The Palm Beach murders : thrillers - Patterson, James, 1947-; Born, James O.; Arnold, Tim (Journalist); Swierczynski, Duane; Patterson, James, 1947-; Patterson, James, 1947-; Patterson, James, 1947- (New York : Grand Central Publishing, 2021)
The Palm Beach murders: Both survivors of the divorce wars, Christy and Martin don't believe in love at first sight and certainly not on a first date. But from the instant they lock eyes, life becomes a sexy, romantic dream come true. That is, until they start playing a strangely intense game of make-believe, a game that's about to go too far.
Nooners: Everyone who knows Tim says he's a good guy. But the popular advertising exec has a problem: a lot of the people who know him are getting murdered. And by the time he figures out why, Tim won't feel so good anymore.
Stingrays: When a teenager goes missing on a Caribbean beach, the local police are baffled. It's up to the Stingrays, a world class team that solves the unsolvable, to unearth the truth: a truth that no one will believe.
The Palm Beach murders / James Patterson with James O. Born -- Nooners / James Patterson with Tim Arnold -- Stingrays / James Patterson with Duane Swierczynski.
"The Palm Beach murders was first published as Let's play make-believe by Little, Brown in August 2016" -- verso.
"Stingrays was first published as an ebook by Little, Brown in June 2017. Nooners was first published as an ebook by Little, Brown in July 2017." -- Verso.
Keywords: Man-woman relationships -- Fiction; Murder -- Fiction; Missing persons -- Fiction; FICTION / Thrillers / Suspense; FICTION / Mystery & Detective / International Crime & Mystery; FICTION / Thrillers / Crime; Man-woman relationships; Missing persons; Murder; Man-woman relationship -- Fiction; Homicide -- Fiction; Missing persons -- Fiction; Palm Beach (Fla.) -- Fiction; Florida -- Palm Beach; Palm Beach (Fla.) -- Fiction; Fiction; Novellas; Thrillers (Fiction); Thrillers (Fiction); Thrillers (Fiction); Novellas